1983
DOI: 10.1037/0096-3445.112.4.616
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation and the attentional demands of letter encoding.

Abstract: The idea that familiar events can be encoded automatically has gained general acceptance in cognitive psychology since Posner and Boies (1971) first reported that reaction times to a secondary probe were not interfered with by letter encoding. More recently, Ogden, Martin, and Paap (1981) used a more valid control for estimating baseline probe performance and found secondary task interference, suggesting that letter encoding does require attentional resources. The present series of experiments began with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
(66 reference statements)
2
15
0
Order By: Relevance
“…Under such circumstances, the secondary task would fail to receive any allocation of attentional space (or it could be performed in the articulatory loop without causing decrements in executive functioning). Similar findings have been reported previously (Johnson, Forester, Calderwood, & Weisberger, 1983). It would be interesting to see the effects with more difficult secondary tasks.…”
Section: Dij'erences Between Add and Control Group (Cg)supporting
confidence: 84%
“…Under such circumstances, the secondary task would fail to receive any allocation of attentional space (or it could be performed in the articulatory loop without causing decrements in executive functioning). Similar findings have been reported previously (Johnson, Forester, Calderwood, & Weisberger, 1983). It would be interesting to see the effects with more difficult secondary tasks.…”
Section: Dij'erences Between Add and Control Group (Cg)supporting
confidence: 84%
“…The experimental tasks followed the paradigm developed by Posner and Boies (1971) and refined by subsequent investigators (Johnson et al, 1983). There were three task conditions, two single-task and one dual-task.…”
Section: Experiments 1 Methodsmentioning
confidence: 99%
“…Subsequent studies (Comstock, 1973;Johnson, Forester, Calderwood, & Weisgerber, 1983;McLeod, 1978;Millar, 1975;Ogden, Martin, & Paap, 1980;Posner & Klein, 1973;Proctor & Fisicaro, 1977;Proctor & Proctor, 1979;Shwartz, 1976) have also demonstrated that matching and response selection are effortful, attention-demanding operations. However, these studies have not unequivocally demonstrated that letter encoding is an attention-free automatic operation.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The results from the change paradigm also have important implications for studies that use responses to auditory probes to assess the resource demands of visual tasks (e.g., Britton & Tesser, 1982;Posner& Boies, 1971), especially when probe reaction times are compared with control conditions in which there is no overt response to the visual task (e.g., the no-letter "control" of Johnson, Forester, Calderwood, &Weisgerber, 1983, andof Ogden, Martin, &Paap, 1980). The present experiments suggest that those results may reflect response competition more than competition for more central resources, contrary to what the authors of those studies concluded.…”
Section: Change Paradigmmentioning
confidence: 99%